Current issues and critical tasks of university science - B. P. Eliseev (Научный вестник МГТУ ГА)
The Moscow State Technical University of Civil Aviation celebrates the 50th anniversary as a well-known scientific and educational center integrated into the national scientific and innovation system. The strategic government initiatives are based on the recognition of scientific and technological achievements as the key factors in the transition of the Russian economy into a qualitatively new development model; the formation of a geopolitical status that determines the country's position in the global economy, the opportunity and conditions for its integration into the world economic system; competitiveness in global high-tech markets. The analysis of the targets results of the State Acts, including the Strategy for Innovative Development of the Russian Federation for the period up to 2020, shows that despite the undertaken efforts, considerable positive changes in state and effectiveness of national science in general as well as university science in particular, have not taken place yet. The planned values of individual indicators (domestic research and development costs, the share of the higher education sector in domestic research costs, scientometric indicators of Russian authors’ publications in the international databases of Scopus and Web of Science, etc.) have not been achieved. The reasons for unsatisfactory dynamics are considered. It is noted that university science is the richest state-resource that means intellectual capital, scientific schools, talented youth, connections with academic research institutes, manufacture and business, which, by means of the appropriate state policy, can make universities the centers for integration of individual subjects of scientific and innovative activity, ensuring a functional connection. The specific aspects of scientific work in industry universities are highlighted. The priority tasks for modernization of research process and innovation activities in MSTUCA are defined in accordance with the University Development Strategy until 2030.